2002
DOI: 10.1177/002215540205001108
|View full text |Cite
|
Sign up to set email alerts
|

Chromogranin A in the Human Gastrointestinal Tract: An Immunocytochemical Study with Region-specific Antibodies

Abstract: S U M M A R YWe studied the immunoreactivity of 12 different region-specific antibodies to the chromogranin A (CgA) molecule in the various neuroendocrine cell types of the human gastrointestinal (GI) tract by using double immunofluorescence techniques. These staining results were compared with others obtained with a commercial monoclonal CgA antibody (LK2H10). G (gastrin)-cells showed immunoreactivity to virtually all region-specific antibodies, but with varying frequency. Most intestinal EC (enterochromaffin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 23 publications
1
34
0
2
Order By: Relevance
“…Production of CgA has also been reported in the myocardium during cardiac disease [10,11], but confirmation of myocardial CgA production in severe sepsis will require a translational investigational program similar to models used to demonstrate myocardial chromogranin production in cardiac disease. Additional sources for CgA release, beyond the adrenergic system and the myocardium, could be the gastrointestinal or the immune system as CgA is produced throughout the gastrointestinal tract [34] and in activated leucocytes [35]. In agreement with some previous studies [11], we also found high CgA levels in patients treated with proton pump inhibitors in the initial phase of severe sepsis.…”
Section: Discussionsupporting
confidence: 91%
“…Production of CgA has also been reported in the myocardium during cardiac disease [10,11], but confirmation of myocardial CgA production in severe sepsis will require a translational investigational program similar to models used to demonstrate myocardial chromogranin production in cardiac disease. Additional sources for CgA release, beyond the adrenergic system and the myocardium, could be the gastrointestinal or the immune system as CgA is produced throughout the gastrointestinal tract [34] and in activated leucocytes [35]. In agreement with some previous studies [11], we also found high CgA levels in patients treated with proton pump inhibitors in the initial phase of severe sepsis.…”
Section: Discussionsupporting
confidence: 91%
“…A parallel is often drawn between VGF and the chromograninsecretogranin family of proteins, because of their selective localisation in secretory granules, as well as their role as precursors of multiple bioactive peptides (Helle 2004). Chromogranins, too, are differentially processed in gastric endocrine cells (Watkinson et al 1991, Watkinson & Dockray 1992, Portela-Gomes & Stridsberg 2002), although to a profile different from the one we observed for VGF peptides. In fact, G cells showed immunoreactivity to virtually all region-specific antibodies to chromogranin A (Portela-Gomes & Stridsberg 2002), as opposed to the limited reactivity of VGF peptides we could demonstrate in such cell type.…”
Section: Discussionmentioning
confidence: 52%
“…1). There may also be species-, cell-and tissue-specific processing of CgA, as in the rat [26] and in the human gastrointestinal tract [27][28][29].…”
Section: The Prohormone Conceptmentioning
confidence: 99%
“…In addition, the specific inhibition of cardiac contractility and the counteraction of the b-adrenergic inotropism were most potently elicited by VS-1, CgA 7-57 and CgA 1 -40SS , implicating the disulfidebridged region as a requirement for the marked negative inotropism whether mechanically activated or stimulated by ISO [43]. Interestingly, the least effective inhibitor, the frog CgA 4-16 is more acidic than the bovine homologue, while there is a complete homology between the frog, porcine, bovine and human CgA [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] and CgA 40-62 [101]. Hence, the modulation of myocardial contractility in the frog heart by structurally different regions of frog and bovine VS-I is consistent with a functional conservation of this domain.…”
Section: Cardiovascular Processes a Range Of Inhibitory Responses To mentioning
confidence: 99%